(untitled) (Revista Rupturas, 2019)
This article pretends to open a critical dialogue between theology and social sciences; so that, it permits to reach consensus that benefits society and mankind. As a result, taking into consideration the approach between theology and social sciences, this document not only debates about the method or methods that must be promoted but also it hopes to explain the hermeneutics as a model for interpretation. Finally, it questions the various ideologies that are current in society.